1999
DOI: 10.1016/s0168-6445(99)00006-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biotechnological aspects of xylanases

Abstract: Hemicellulolytic microorganisms play a significant role in nature by recycling hemicellulose, one of the main components of plant polysaccharides. Xylanases (EC 3.2.1.8) catalyze the hydrolysis of xylan, the major constituent of hemicellulose. The use of these enzymes could greatly improve the overall economics of processing lignocellulosic materials for the generation of liquid fuels and chemicals. Recently cellulase-free xylanases have received great attention in the development of environmentally friendly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
285
1
35

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(325 citation statements)
references
References 168 publications
(215 reference statements)
4
285
1
35
Order By: Relevance
“…The binding of insoluble materials to cells plays an important role in the efficiency of the enzymatic hydrolysis of insoluble lignocellulosic biomass. Therefore, these results suggest that strain MF28 has an essential component that anchors cells to xylan, such as a xylan-binding domain (XBD) (Kulkarni et al, 1999). To further understand the binding domains, quantitative reverse transcription PCR was conducted to measure the expression of putative binding genes in strain MF28.…”
Section: Contribution Of Xylan-binding Domain To Overall Uptake Of Xylanmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of insoluble materials to cells plays an important role in the efficiency of the enzymatic hydrolysis of insoluble lignocellulosic biomass. Therefore, these results suggest that strain MF28 has an essential component that anchors cells to xylan, such as a xylan-binding domain (XBD) (Kulkarni et al, 1999). To further understand the binding domains, quantitative reverse transcription PCR was conducted to measure the expression of putative binding genes in strain MF28.…”
Section: Contribution Of Xylan-binding Domain To Overall Uptake Of Xylanmentioning
confidence: 99%
“…5C). Naturally occurring ''xylano somes'' are self-assembled complexes present on the cell surface, comprising a multimodular non-catalytic scaffold in protein and containing at least one carbohydrate-binding domain (e.g., XBD) which targets the catalytic domains toward saccharification of complex biomass substrates (Kulkarni et al, 1999). The high expression of members of the xbd gene family in strain MF28 strongly suggests that a xylan-binding domain/module contributes to carbohydrate-cell binding.…”
Section: Contribution Of Xylan-binding Domain To Overall Uptake Of Xylanmentioning
confidence: 99%
“…In order to meet these demands, the genes of the enzymes in question are overexpressed in heterologous hosts like ascomycetous yeasts (Saccharomyces cerevisiae, Pichia pastoris) or filamentous ascomycetes (Aspergillus spp., Trichoderma sp.). This approach is successfully applied with hydrolytic enzymes from ascomycetous species (Kulkarni et al 1999), but was repeatedly shown to be problematic for enzymes from wood-decaying basidiomycetes due to differences in protein glycosylation (e.g. see , Larrondo et al 2003a.…”
Section: Screening For New Enzmyes New Versions Of Well Known Enzymesmentioning
confidence: 99%
“…Important for this is that the enzymes are as much as possible cellulase-free (Christov et al 1999). Also for applications in the textile industry, presence of cellulases is unwanted in xylanase preparations in order not to damage the celluose (Kulkarni et al 1999. Production conditions, in particular media components, can favour which types of enzymes are obtained from the fungi and help to avoid or reduce impurities with unwanted enzymes (Haltrich et al 1996).…”
Section: Xylanasesmentioning
confidence: 99%
“…Extracellular hydrolytic enzymes such as amylases, proteases, lipases and DNases, have quite diverse potential usages in different areas such as food industry, feed additive, biomedical sciences and chemical industries [5][6][7][8]. Industrial processes are carried out under specific physical and chemical conditions which cannot always be adjusted to the optimal values required for the activity of the available enzymes.…”
Section: Introductionmentioning
confidence: 99%